The Effect Of Training And Work Discipline On Employee Performance At Astera Hotel Bintaro In South Tangerang City - Teul Panda Banjal; Muhammad Tegar Irsyadi; Ruli Haris; Riki Haryono; Harun Indra Kusuma; Agung Tri Putranto (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2026)
This study aims to determine the effect of training and work discipline on employee performance at Astera Hotel Bintaro in South Tangerang City. The method used is explanatory research with sampling using saturated samples where all members of the population are used as samples so that the sample in this study amounted to 82 respondents and the data analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study indicate that training has a positive and significant effect on employee performance as evidenced by the hypothesis test obtained t count > t table or (8.758 > 1.990) with an influence contribution of 49.0%. Work discipline has a positive and significant effect on employee performance as evidenced by the hypothesis test obtained t count > t table or (7.071 > 1.990) with an influence contribution of 38.5%. Training and work discipline simultaneously have a positive and significant effect on employee performance as evidenced by the hypothesis test obtained F count > F table or (49.407 > 3.110) and obtained the regression equation Y = 9.303 + 0.465X1 + 0.305X2 and has an influence contribution of 55.6%.